2005
DOI: 10.1002/eat.20167
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with bulimia nervosa and eating disorder not otherwise specified-purging only

Abstract: Results prompt reappraisal of current criteria of BN to encompass those who purge without binge eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 14 publications
8
83
1
2
Order By: Relevance
“…This research replicates a growing body of work, 4,5,7,8,14 which has shown that the group of patients who purge in the absence of objective binge episodes closely resembles those with BN P. The EDNOS purging only patients reported as much psychological disturbance on the EDI and Rosenberg self-esteem inventory as did those with BN P. Although the purging only group reported higher levels of depression than the BN P, both groups had very high scores and at these elevated levels of depression the difference in depression scores is likely not clinically noticeable. As well, previous research 8 suggests that differences between these groups on depression may not be stable.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This research replicates a growing body of work, 4,5,7,8,14 which has shown that the group of patients who purge in the absence of objective binge episodes closely resembles those with BN P. The EDNOS purging only patients reported as much psychological disturbance on the EDI and Rosenberg self-esteem inventory as did those with BN P. Although the purging only group reported higher levels of depression than the BN P, both groups had very high scores and at these elevated levels of depression the difference in depression scores is likely not clinically noticeable. As well, previous research 8 suggests that differences between these groups on depression may not be stable.…”
Section: Resultssupporting
confidence: 84%
“…2 A number of recent articles have focused on identifying subgroups of individuals within the broader EDNOS category. [3][4][5][6][7][8] In general, the small literature suggests that there may be justification to relax the current diagnostic boundaries between full syndrome BN and subsyndromal BN. 3,6,9 In addition, there appears to be a clinically significant subgroup of EDNOS patients with a purging only form of eating disorder-EDNOS P, 4,7,8 who both resemble and exhibit differences from patients with BN purging subtype (BN P).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examined purging solely in the context of AN or BN were not reviewed in detail. A total of 14 articles were identified, [5][6][7][8][9][10][11][12][13][14][15][16][17][18] reflecting 10 separate samples of PD. A challenge in reviewing the literature of a condition which has not been formally named or defined is heterogeneity of names and definitions used for the syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 presents the various names and definitions used across studies included in the review. Notably, the same name (EDNOS-P) has been paired with disparate definitions, 11,15 and no studies appear to have used the same definition. The term ''purging disorder'' is used in the current article because it neither assumes a close relation between PD and BN as reflected by the term ''subjective bulimia nervosa'' 7 and because EDNOS means ''eating disorder not otherwise specified'' which seems inherently contradictory to specifying a syndrome characterized by recurrent purging.…”
Section: Methodsmentioning
confidence: 99%
“…The internal reliability of the measure is high (Cronbach's alpha = 0.90; see Peterson et al, 2007). The EDE-Q is widely with adults with eating disorders and has demonstrated validity in the assessment of adolescents with eating disorders (Binford and LeGrange, 2005).…”
Section: Eating Disorder Examination-questionnaire (Edeq)mentioning
confidence: 99%